A unique biomass based integrated energy system for cleaner production of multiple energy outputs for sustainable communities. (February 2023) - Karaca, Ali Erdogan; Dincer, Ibrahim; Nitefor, Michael
Highlights: A unique waste-to-energy system is developed and comprehensively analyzed. Thermodynamic techniques are practiced for system's performance evaluation. Sensitivity analyses are conducted on critical design and operational parameters. Energetic and exergetic efficiencies are evaluated as 67.25% and 45.16%. Abstract: Development of integrated energy systems where food wastes are converted into useful forms of energy is critical for establishing sustainable communities. In this study, a unique integrated energy system is developed and comprehensively analyzed to provide clean and sustainable electricity, biomethane, hydrogen, and heating from organic biomass energy and off-peak period excess electricity. An application of the developed system is considered for the Durham Region in Ontario, Canada. The organic food wastes collected under the Durham's green bin program are anaerobically digested to produce biogas. A high-pressure water scrubbing technique is utilized to upgrade the produced biogas to high purity biomethane. Excess electricity available during off-peak energy periods in the region is utilized for hydrogen production via proton exchange membrane water electrolysis. The produced biomethane and hydrogen is blended to synthesize an energy-dense fuel that is considered for power and heat generation via a combined regenerative gas-steam power cycle as well as a cleaner fuel for public transit buses in the region. On an annual basis, the proposed system provides about 1966 tons of biomethane from food wastes and about 298 tons of H2 from excess off-peak electricity in the Durham Region. Furthermore, the current integrated system is capable of producing 10.72 MW of electricity and 7.5 MW of heat for space heating and hot water applications. The overall energetic and exergetic efficiencies of the system are obtained as 67.25% and 45.16%, respectively. Graphical abstract: Image, graphical abstract